Developing and piloting a self-assessment tool for medication review competence of practicing pharmacists based on nationally set competence criteria - Noora Lias; Tanja Lindholm; Marika Pohjanoksa-Mäntylä; Aleksi Westerholm; Marja Airaksinen (BMC, 2021)
Abstract Background New competence requirements have emerged for pharmacists as a result of changing societal needs towards more patient-centred practices. Today, medication review competence can be considered as basic pharmaceutical competence. Medication review specific competence criteria and tools for self-assessing the competence are essential in building competences and a shared understanding of medication reviews as a collaborative practice. The aim of this study was to develop and pilot a self-assessment tool for medication review competence among practicing pharmacists in Finland. Methods The development of the self-assessment tool was based on the national medication review competence criteria for pharmacists established in Finland in 2017 and piloting the tool among practicing pharmacists in a national online survey in October 2018. The pharmacists self-assessed their medication review competence with a five-point Likert scale ranging from 1 for "very poor/not at all" to 5 for "very good". Results The internal consistency of the self-assessment tool was high as the range of the competence areas' Cronbach's alpha was 0.953-0.973. The competence areas consisted of prescription review competence (20 items, Cronbach's alpha 0.953), additional statements for medication review competence (11 additional items, Cronbach's alpha 0.963) and medication review as a whole, including both the statements of prescription review and medication review competence (31 items, Cronbach's alpha 0.973). Competence items closely related to routine dispensing were most commonly self-estimated to be mastered by the practicing pharmacists who responded (n = 344), while the more clinical and patient-centred competence items had the lowest self-estimates. This indicates that the self-assessment tool works logically and differentiates pharmacists according to competence. The self-assessed medication review competence was at a very good or good level among more than half (55%) of the respondents (n = 344). Conclusion A self-assessment tool for medication review competence was developed and validated. The piloted self-assessment tool can be used for regular evaluation of practicing pharmacists' medication review competence which is becoming an increasingly important basis for their contribution to patient care and society.